Gender Discrimination in the Primary School English Language Textbooks in Tamil Nadu - R.M, Dr Amruthraj (THE PRIMARY TEACHER, 2012)
For a great majority of school-going children, as also for teachers, school textbooks are the only accessible and affordable resource for education. Thus, the textual material that is developed for the school-going children is of paramount importance in education. It is the textbook that they are exposed to in the classroom, and the teacher conveys its meaning and interpretation, while embossing his/her own ideas on the minds of children, who are yet in the formative stage. This is one of the earliest and most important influences on the young, growing minds. School textbooks and curriculum influence gender roles of students immensely. This paper explores the English language textbooks taught in Government primary schools in Tamil Nadu through a gender sensitive perspective. It is quite clear from the analysis of the textbooks that despite an explicit policy of gender sensitization of school curriculum, gender stereotypes and gender bias still exists. It points to the need of preparing gender sensitive textbook material based on feminist knowledge base.